Information sought, information shared: exploring performance and image enhancing drug user-facilitated harm reduction information in online forums - Boden Tighe; Matthew Dunn; Fiona H. McKay; Timothy Piatkowski (BMC, 2017)
Abstract Background There is good evidence to suggest that performance and image enhancing drug (PIED) use is increasing in Australia and that there is an increase in those using PIEDs who have never used another illicit substance. Peers have always been an important source of information in this group, though the rise of the Internet, and the increased use of Internet forums amongst substance consumers to share harm reduction information, means that PIED users may have access to a large array of views and opinions. The aim of this study was to explore the type of information that PIED users seek and share on these forums. Methods An online search was conducted to identify online forums that discussed PIED use. Three discussion forums were included in this study: aussiegymjunkies.com, bodybuildingforums.com.au, and brotherhoodofpain.com. The primary source of data for this study was the 'threads' from the online forums. Threads were thematically analysed for overall content, leading to the identification of themes. Results One hundred thirty-four threads and 1716 individual posts from 450 unique avatars were included in this analysis. Two themes were identified: (1) personal experiences and advice and (2) referral to services and referral to the scientific literature. Conclusions Internet forums are an accessible way for members of the PIED community to seek and share information to reduce the harms associated with PIED use. Forum members show concern for both their own and others' use and, where they lack information, will recommend seeking information from medical professionals. Anecdotal evidence is given high credence though the findings from the scientific literature are used to support opinions. The engagement of health professionals within forums could prove a useful strategy for engaging with this population to provide harm reduction interventions, particularly as forum members are clearly seeking further reliable information, and peers may act as a conduit between users and the health and medical profession.